A Mobile App Deployment for Quality-of-Life Patient with Thalassemia: A narrative review - Afifah Ayu; Sigit Mulyono (Universitas Muhammadiyah Surakarta, 2023)
Thalassemia is a hereditary hemolytic anemia disease that is inherited from parents. Occurs due to the inability of red blood cells to form hemoglobin. Thus causing thalassemia patients to undergo transfusion therapy for life. The mobile application contains detailed information about thalassemia that can be easily accessed by thalassemia patients and their families aiming to maintain the quality of life of patients with thalassemia. The purpose of this literature review is to determine the effectiveness of mobile applications applied to the quality of life of patients thalassemia. The method used in this preparation is by electronic search of online databases, namely: Google Scholar Science Direct, PROQUEST. The criteria for writing are full text and publications in 2018-2022. Research search found 10 articles had been extracted. The results obtained are mobile applications for the quality of life of patients with thalassemia have a positive response and dynamically need to be developed.